2022
DOI: 10.31083/j.fbs1404028
|View full text |Cite
|
Sign up to set email alerts
|

Disease Characteristics and Psychiatric Comorbidities in Adolescents with Anorexia Nervosa Hospitalized During COVID-19 Pandemic

Abstract: Background: Since the beginning of COVID-19 pandemic, an increase in new diagnoses and pediatric hospital admission for anorexia nervosa (AN) or atypical AN in adolescents have been reported, suggesting an adverse effect of COVID-19 on youth mental health. We hypothesized possible differences in prevalence of hospitalization and/or disease severity, related to socio-economic status and/or ethnicity. Methods: Retrospectively, patients were divided into two subgroups and compared according to the date of first h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our results are in contrast with Girardi M et al who found out more intravenous fluids, oral dietetic supplements and enteral nutrition by nasogastric tube in post Covid-19 period than before the onset of pandemic. Moreover, the same group presented higher prevalence of psychiatric comorbidities and required most frequently treatments with psychotropic drugs [ 15 ]. Nevertheless, our result is in line with Goldberg et al who reported a 35% reduction in median hospitalization duration even if there was a significant increase in the number of adolescents hospitalized with AN [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in contrast with Girardi M et al who found out more intravenous fluids, oral dietetic supplements and enteral nutrition by nasogastric tube in post Covid-19 period than before the onset of pandemic. Moreover, the same group presented higher prevalence of psychiatric comorbidities and required most frequently treatments with psychotropic drugs [ 15 ]. Nevertheless, our result is in line with Goldberg et al who reported a 35% reduction in median hospitalization duration even if there was a significant increase in the number of adolescents hospitalized with AN [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…(i) Socio-demographic characteristics: Age, sex, working status, child's age, and nationality. The working status was classified according to the Italian National Institute of Statistics criteria, which is entirely cross-linkable with the International Standard Classification of Occupations (as we previously reported [22]) and was grouped into two levels: low (unoccupied, unskilled, and semi-skilled workers, manual workers, and craftsmen) and high (legislators, senior officials and managers, professionals, technicians, associate professionals, sales workers, small business and farm owners, administrators, and higher executives). (ii) IHP implementation was evaluated in terms of daily practices at school by using closed (yes/no) and multiple choice questions.…”
Section: Parents and School Staff's Surveymentioning
confidence: 99%
“…This underlines the necessity for further research on ED in children and youth in the context of the COVID-19 pandemic. Local studies found increases in pediatric hospital admissions for ED in Canada ( 19–21 ), North America ( 22–24 ), Australia ( 25 ), Israel ( 26 ), Italy ( 27 , 28 ), Norway ( 29 ), and the Netherlands ( 30 ) following the onset of the COVID-19 pandemic. Findings concerning symptom severity or clinical characteristics of children and youth admitted for ED treatment during the COVID-19 pandemic have been diverse: North-American, Canadian and Italian pediatric departments at tertiary care hospitals with special ED-treatment programs registered more critical somato-medical problems ( 19 , 20 , 23 , 24 , 28 ), whereas similar medical facilities in Australia ( 25 ) and Israel ( 26 ) found clinical characteristics to be unchanged to pre-COVID-19 samples.…”
Section: Introductionmentioning
confidence: 99%
“…Local studies found increases in pediatric hospital admissions for ED in Canada ( 19–21 ), North America ( 22–24 ), Australia ( 25 ), Israel ( 26 ), Italy ( 27 , 28 ), Norway ( 29 ), and the Netherlands ( 30 ) following the onset of the COVID-19 pandemic. Findings concerning symptom severity or clinical characteristics of children and youth admitted for ED treatment during the COVID-19 pandemic have been diverse: North-American, Canadian and Italian pediatric departments at tertiary care hospitals with special ED-treatment programs registered more critical somato-medical problems ( 19 , 20 , 23 , 24 , 28 ), whereas similar medical facilities in Australia ( 25 ) and Israel ( 26 ) found clinical characteristics to be unchanged to pre-COVID-19 samples. Shortened length of stay (LOS) was found at pediatric hospitals in Israel and Italy ( 26 , 27 ), yet prolonged LOS was observed at a large pediatric hospital with a specialized ED-treatment program in North America and at some Departments of Child and Adolescent Psychiatry in European Countries ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation